Joshua - Mathews, K. A. (Grand Rapids, Michigan : Baker Books, 2016)
The Teach the Text Commentary Series gives pastors the best of biblical scholarship and presents the information needed to move seamlessly from the meaning of the text to its effective communication. By providing focused commentary, this volume allows pastors to quickly grasp the most important information. Each unit of the commentary includes the big idea and key themes of the passage; sections dedicated to understanding, teaching, and illustrating the text; and full-color illustrations, maps, and photos. Joshua covers a critical period in the history of Israel, as God brings them out of the desert wanderings into the land he promised them, through a series of spectacular military maneuvers. Yet readers today may struggle with commands from God that offend modern sensibilities. And what does the conquest and division of the promised land have to do with the Christian life? Professor Kenneth Mathews helps teachers, preachers, and everyday readers understand this important Old Testament book in its original context and apply it for today. While Joshua is historical, it is also theological. The crucial lessons then and now are that God's word is truthful and authoritative and that he fulfills his promises. -- from the back cover.
Introduction to Joshua -- Joshua 1:1-18: Preparing to possess the land -- Joshua 2:1-24: Scouting the land -- Joshua 3:1-17: Crossing the Jordan -- Joshua 4:1-24: Remembering God's grace -- Joshua 5:1-12: New life in Canaan -- Joshua 5:13-15: The commander of Israel's Armies -- Joshua 6:1-27: Jericho falls -- Additional insights: Joshua's jihad? -- Joshua 7:16-26: Achan's punishment -- Joshua 8:1-29: Victory at Ai -- Joshua 8:3-35: God's covenant word in the land -- Joshua 9:1-27: Gibeonite deception -- Joshua 10:1-15: The sun stood still -- Additional Insights: The sun "stood still" -- Joshua 10:16-43: Victory over the Southern kings -- Joshua 11:1-15: Defeat of the Northern kings -- Joshua 11:16-12:24: Summing up the conquest -- Joshua 13:1-33: The Transjordan land -- Joshua 14:1-15: Caleb's inheritance -- Joshua 15:1-63: Judah's inheritance and Caleb's family -- Joshua 16:1-17:18: Joseph's inheritance -- Joshua 18:1-19:51: Inheritance for the remaining tribes -- Joshua 20:1-9: Cities of refuge -- Joshual 21:1-42: The Levites' towns -- Joshua 21:43-45: Rest in the land -- Joshua 22:1-9: Transjordan tribes receive a blessing -- Joshua 22:10-34: Threat to unity -- Joshua 23:1-11: A call to faithfulness -- Joshua 23:12-16: Words of warning -- Joshua 24:1-18: Covenant renewal -- Joshua 24:19-28: Covenant confirmed -- Joshua 24:29-33: Funerals in faith. Notes. Bibliography.
Includes bibliographical references (pages 211-213) and index.
Keywords: Bible. -- Commentaries; Bible. Joshua - Commentaries; Commentaries